Effect of a nano-ceramic mold coating on the fluidity length of thin-wall castings in Al4-1 alloy gravity sand casting - Borouni, Mansour (Materiali in tehnologije, 2014)
The thin-wall casting of aluminum alloys provides new opportunities for aerospace industries in producing lightmass structures with good mechanical properties. The fluidity of molten metal is very important in producing sound castings, particularly thin-wall castings. In the gravity casting of thin-wall castings of the Al4-1 alloy, the melt that fills the mold with the effect of self-weight, does not have sufficient fluidity, so causing defects such as cold shut, misrun and shrinkage defects during the solidification. These defects reduce the quality and mechanical properties of the cast parts. The casting fluidity depends on many factors, such as temperature, melt composition, casting part shape and mold coating. This study reports the influence of a nano-ceramics mold coating, a micro-ceramic mold coating, a graphite mold coating and the section thickness of the part on the fluidity length of Al4-1 alloy castings. The results showed that by applying nano-ceramic mold coatings on the surface of a sand mold, the fluidity length and the surface quality of the castings can be improved.
Keywords: aluminijeve zlitine; aluminium alloy; aluminium alloys; nano ceramic coating; nanokeramični premaz; micro ceramic coating; mikrokeramični premaz; fluidity length; tekočnost; thin wall castings; tankostenski ulitki